Techno-Economic Analysis of Decisions to Upgrade Gas Turbine Blade Models: A Comparative Case Study of the Investment Value of Upgrading The Row 1 Blades of a 130 MW Gas Turbine - Muhammad Hizbullah Abrori (Journal Research of Social Science, Economics, and Management, 2026)
This study aimed to conduct a techno-economic analysis of the decision to upgrade the Blade 1 component to the MXL type in a gas turbine unit by comparing the investment schemes for Gas Turbine (GT) 21 and GT 13. In 2021, GT 21 required an upgrade to MXL technology because it had reached its end of service life, whereas GT 13 was scheduled for repair because it still had remaining operational life. The methodology involved a comprehensive comparison of the two expenditure schemes over the 2014–2031 period, considering investment costs, repair costs, and operational profit values. Performance test evaluations showed that MXL technology applied to GT 21 increased efficiency by 0.18%. This efficiency improvement contributed to reduced natural gas consumption and increased electricity production, generating a total financial benefit of more than IDR 6 billion during the 2021–2025 period. Despite the potential efficiency improvements, the financial analysis of the GT 13 case showed that the total net cost of the upgrade scheme reached IDR 71,658,492,352.67 after accounting for efficiency gains. This value was higher than the repair scheme, which required a total cost of IDR 66,297,933,022.57. The findings confirm that maintaining the repair scheme for GT 13 was the most financially advantageous decision, as the company avoided additional investment expenditure of IDR 5,360,559,330.10 compared with implementing the upgrade program.